Standardised or individualised X-ray tube angle for mediolateral oblique projection in digital mammography?. Issue 3 (August 2022) - Moshina, N.; Bjørnson, E.W.; Holen, Å.S.; Larsen, M.; Hansestad, B.; Tøsdal, L.; Hofvind, S.
Abstract: Introduction: We aimed to investigate whether there were any differences in positioning criteria related to the presentation of the pectoralis major muscle (pectoral muscle) for women of different heights using a standardized 60° X-ray tube angle for mammograms in mediolateral oblique (MLO) projection. Methods: Data from MLO mammograms of right breasts of 45, 193 women screened in BreastScreen Norway 2016–2019 were used. The positioning criteria were related to the pectoral muscle length (measure A and measure B), width and shape and considered adequate or inadequate depending on the degree of fulfilling the criteria. Data associated with the pectoral muscle were extracted from Volpara, an automated software for breast density assessment. Information on height was obtained from a self-reported questionnaire received by the women together with the invitation to attend the screening program. Women were divided into three groups based on the height percentiles (P) in the Norwegian growth curves: < 25th percentile (<P25th: ≤163 cm), 25th-75th percentile (P25–P75th: 164–170 cm), and >75th percentile (>P75th: >170 cm). Logistic regression was used to analyse the odds of adequate pectoral muscle length A and B, and shape, adjusting each model for screening technique and equipment model. Results were presented with odds ratios (OR) and 95% confidence intervals (CI). Results: Mean age of the screened women was 61.5 (SD = 4.8) years. The adequate measure for the pectoral muscle length A was obtained for 25.9% (11, 724/45, 193), length B for 76.3% (34, 489/45, 193), width for 75.0% (33, 894/45, 193) and shape for 97.6% (44, 118/45, 193) of the mammograms. Adjusted odds of an adequate pectoral muscle length A were lower for women of <P25th (OR = 0.90, 95% CI: 0.86–0.95) compared to women of P25-75th. Odds of an adequate pectoral muscle length B were lower for women of <P25th (OR = 0.88, 95% CI 0.84–0.93) and higher for women of >P75th (OR = 1.08, 95% CI 1.02–1.14) compared to women of P25-75. Odds of an adequate pectoral muscle shape were higher for women of <P25th (OR = 1.14, 95%CI 1.08–1.19) and lower for women of >P75th (OR = 0.92, 95% CI 0.87–0.97) compared to women of P25-75th. Conclusion: The 60° X-ray tube angle might suit most of the female population offered mammographic screening in Norway, but women of a relatively low height (163 cm or lower) might benefit from an X-ray tube angle less than 60-degrees. Implications for practice: Using 60° X-ray tube angle for the MLO mammograms in BreastScreen Norway fit the majority of the participating women. More research is needed to change the protocol associated with the tube angle for women shorter than 163 cm.